Hypercholesterol Care Movement for Study Mothers in Gang Rempong South Jakarta - Royani Chairiyah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Hypercholesterolemia is a common metabolic condition characterized by high blood plasma cholesterol levels and can be a risk factor for developing cardiovascular disease. The proportion is more women than men. But not all people know the causes, risk factors, long-term health impacts and prevention methods including solutions. The purpose of this activity is to increase awareness of mothers studying hypercholesterol. The method of activity was given in the form of providing health education and checking blood pressure and cholesterol which was carried out directly at one of the houses of the recitation mothers of gang rempong, South Jakarta. From the results of the service, it was concluded that 1) The knowledge of study mothers increased by 14.4% with pre-test results 76, posttest 89. 2) 5 people who had elevated blood pressure or suspected hypertension (20.27%) and 3 people who had hypercholesterolemia (21.62%). Advice with a healthy lifestyle and good diet can prevent hypercholesterol.